1997
DOI: 10.1002/(sici)1520-6343(1997)3:6<469::aid-bspy6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Removal of spectral noise in the quantitation of protein structure through infrared band decomposition

Abstract: The underlying noise in the infrared spectra of proteins may introduce artifacts in the quantitation of proteins by curve‐fitting of the amide I band. Smoothing methods are able to reduce the noise but can introduce alterations in band shape that affect the information contained in the spectrum. Three methods to remove noise—Savitzky‐Golay, Fourier filtering, and maximum entropy—have been used to ascertain their influence on the quantitative information when applied to protein bands. Use of artificial curves s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…Buffer contribution was subtracted from the individual spectra and spectral noise was reduced as described previously (29). The protein secondary structure was estimated from 600 scans of IR spectra by decomposition of the amide IЈ band into its spectral components (29). For temperature-dependent studies, the samples were submitted to heating cycles at each at the indicated temperatures.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Buffer contribution was subtracted from the individual spectra and spectral noise was reduced as described previously (29). The protein secondary structure was estimated from 600 scans of IR spectra by decomposition of the amide IЈ band into its spectral components (29). For temperature-dependent studies, the samples were submitted to heating cycles at each at the indicated temperatures.…”
Section: Methodsmentioning
confidence: 89%
“…Routinely, infrared spectra were taken in triplicate from different KcsA samples in a Bruker IF66s instrument equipped with a DTGS detector. Buffer contribution was subtracted from the individual spectra and spectral noise was reduced as described previously (29). The protein secondary structure was estimated from 600 scans of IR spectra by decomposition of the amide IЈ band into its spectral components (29).…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, the differences among the three experiments were lower than 5%. The error in estimation of the percentage of secondary structure depends mainly on the removal of spectral noise, and it was estimated to be 2% (20). For the measurement of the tyrosine ring vibration wave number, an exponential baseline was subtracted.…”
Section: Methodsmentioning
confidence: 99%
“…Spectra smoothing was carried out applying the maximum entropy method, assuming that noise and band shape follow a normal distribution. The minimum bandwidth was set to 12 cm Ϫ1 (8). The signal/noise ratio of the processed spectra was better than 11000:1.…”
Section: Fig 1 Sequence Alignmentmentioning
confidence: 99%
“…Protein secondary structure was quantified by band deconvolution of the amide I band (8,12). The number and position (wave number) of the bands were taken from the deconvoluted spectra; the bandwidth was estimated from the derived spectra; and the height band taken from raw spectra (13).…”
Section: Fig 1 Sequence Alignmentmentioning
confidence: 99%